The Influence of Art Therapy, Growth Mindset, and Mindfulness Practices in Reducing Teacher Anxiety: A Mixed-Methods Approach - Robertus Heru Setyo Suhartono; Yustina Sapan; Indrojiono Indrojiono; Asmi Ode; Pierre Marcello Lopulalan (PT FORMOSA CENDEKIA GLOBAL, 2026)
Teacher anxiety is a growing challenge in contemporary education, particularly as educators are expected to integrate mindfulness practices while managing complex emotional demands. This study examines the effects of an integrative intervention combining art therapy, growth mindset practices, and mindfulness on reducing teacher anxiety through enhanced emotional regulation. Using a mixed-methods sequential explanatory design, the findings show a significant reduction in anxiety and improved emotional regulation among participating teachers, with emotional regulation identified as a key mediating mechanism. The results highlight the value of integrating creative, cognitive, and self-awareness–based approaches as an evidence-based strategy for strengthening teachers’ emotional well-being in mindfulness-oriented classroom contexts.